Active land policy in small municipalities in the Netherlands: "We don't do it, unless...". (September 2018) - van Oosten, Thomas; Witte, Patrick; Hartmann, Thomas
Abstract: Due to their active role in land development, Dutch municipalities have suffered considerably from the economic crisis. The financial and economic effects are particularly striking in small municipalities. We conducted an empirical analysis to highlight the magnitude of the financial effects both pre- and post-crisis and to determine the potential reasons for these differences in small Dutch municipalities. Aside from the main reasons, such as housing demand stagnation and declining land prices, some additional causes are specifically responsible for the struggles of small Dutch municipalities. These causes include a downward adjustment of housing building, optimistic acting of municipalities and political motives. Furthermore, several contextual causes have led to financial disappointments. Dutch land policy is an extreme example of active land policy as municipalities are heavily involved in the development of land, which seems to be partly inspired by reasons related to ideology, the institutional framework and enrichment strategies. The lessons from the Netherlands can be seen as an indicator for other countries who are conducting or experimenting with forms of active land policy.